Optimizing of Transmission Gear Ratio based on Cruise-Isight Co-simulation - Ai Xiaochen; Zheng Guangyong; Zhang Shoufeng; Zeng Hao (Jixie chuandong)
In order to improve fuel economy further within traction ability target,a Cruise-Isight Co-simulation model is established. By using multi-island genetic algorithm,the transmission gear ratio is optimized separately under certain traction ability and structural design constraints,a basic optimized scheme which can meets performance target is gotten. The gear ratio result from optimization model is adjusted according to drive comfort and structural requirements from the engineering point of view. Finally,the gear ratio is recommended which can meets traction and engineering requirements. After optimization,the traction performance reaches target closely and the integrated fuel consumption of NEDC cycle is reduced by 0. 23 L/100 km,3. 86%lower than the original scheme,and the ride comfort of the constant speed shift is improved also.